A recurrent concealed parahisian accessory pathway. Issue 6 (17th April 2018) - Verbeet, Thierry; Castro, Jose; Almorad, Alexandre
Key Clinical Message: This case demonstrates the interest of ablating in the aortic root in case of resistant parahisian accessory pathways with failure of the right side approach. Failure on the right side may be due to fear of creating an AV block of failure to ablate critical fibers in the parahisian position. Abstract : This case demonstrates the interest of ablating in the aortic root in case of resistant parahisian accessory pathways with failure of the right side approach. Failure on the right side may be due to fear of creating an AV block of failure to ablate critical fibers in the parahisian position.